Effects of cause-related ads on ethical consumption: An experimental approach - Zhao, Xinsheng; Park, Yoon Joo; Yoon, Sung Joon (Nurture, 2024)
Purpose: In light of the rapid proliferation of socially responsible corporate practices, this study aims to verify the effects of cause-related ads. Specifically, we seek to investigate four factors that influence the effectiveness of cause-related ads: customers’ perception of cause-related ads, brand-consumer relationships, brand attachment, and loyalty. Design/Methodology/Approach: This study conducted a combination of experimentation and a questionnaire survey on 324 undergraduate students in an in-class setting. Pretests were performed on 100 participants to select two video ads featuring two different themes with contrasting appeals (rational vs. affective). Findings: The result shows that customers’ perception of cause-related ads positively influenced the consumer-brand relationship. In addition, the brand-consumer relationship significantly influenced brand attachment and customer loyalty. Conclusion: This result confirms that corporate social responsibility activities or cause-related ads form a favorable corporate image, resulting in a positive relationship with the company’s product or service brand, repurchase or repurchase of the company’s products, and positive word of mouth. Practical Implications: The result suggests that the formation of an amicable image with brands through attachment to corporate brands can increase corporate love and loyalty. Therefore, to create highly loyal customers, companies will need to create a favorable image through a continuous influx of socially responsible ads.